PERAN ADVOKAT DALAM MEWUJUDKAN KEADILAN DI SISTEM PERADILAN ADVERSARIAL INDONESIA - Ramot BATUBARA (Jurnal Hukum Lex Generalis, 2023)
In the adversarial justice system in Indonesia, advocates play an important role in realizing justice for the parties involved in the legal process. As legal representatives, advocates serve to ensure that their clients receive equal protection of legal rights. The role of advocates in realizing justice in the Indonesian adversarial justice system is very important. Advocates act as legal advisors who help suspects, defendants, and convicts understand the legal process and ensure that their rights are not violated. Advocates act as a counterweight to the coercive efforts of law enforcement, maintaining justice and the supremacy of law. In Law No. 18 of 2003. This study aims to analyze and highlight the importance of the role of advocates in the context of adversarial justice in Indonesia and its impact on law enforcement and human rights protection. Keywords: Advocate, Role of Advocate, adversarial justice system